COMMUNICATIVITY OF AUTISTIC STUDENT UTTERANCE IN LEARNING INTERACTIONS - Suparno Suparno; Novi Eka Susilowati; Ary Fawzi; Trisna Andarwulan; Astri Widyaruli Anggraeni (Jurusan Sastra Indonesia, 2018)
The purpose of this study is to describe speech communication by autistic students atthe SDLB Autism Laboratory of Universitas Negeri Malang. This study wasconducted on seven autistic students who had different types of autism. The data ofthis study are the elicitation of verbal data in the form of grammatical lingual units andlingual units of the interaction of oral speech of autistic students in the form of wordsand sentences accompanied by speech context. The results of the study show fourthings. First, the shift of speech between teachers and students does not occur wellbecause students are slow in responding to the stimulus from the teacher. Secondly,almost never occurs speech initiation from students. Third, there is inaccuracy andincompatibility of speech responses to stimulus speech. Fourth, the communication ofeach autistic student is different.